2000
DOI: 10.1108/03090560010342610
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ country‐of‐origin (COO) perceptions of imported products in a homogenous less‐developed country

Abstract: In recent years, consumers worldwide have been having increased access to a wide variety of products and services from other countries. Furthermore, with advances in satellite communication, travel, television outreach and Internet access as well as increased education, consumers all over the world are becoming more aware of the products/services available throughout the world. As a result, the significance of products' county-of-origin images in influencing consumer behavior is increasing rapidly. An understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
150
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(165 citation statements)
references
References 29 publications
8
150
0
7
Order By: Relevance
“…COO has also been shown to influence consumer preferences (Knight and Calantone, 2000) and purchase intentions (Kim and Pysarchik, 2000). In addition, COO effects have been observed with products in general (Kaynak et al, 2000;Leonidou et al, 1999) as well as with specific product categories (Kim and Pysarchik, 2000;Teas and Agarwal, 2000) and both as regards the behaviour of individual consumers and that of organizational buyers (Ahmed and d'Astous, 1995). Recent research (Laroche et al, 2005;Pereira et al, 2005) using structural equation modelling contends that COO evaluations are part of a larger "COO image" construct consisting of cognitive, affective and conative components.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…COO has also been shown to influence consumer preferences (Knight and Calantone, 2000) and purchase intentions (Kim and Pysarchik, 2000). In addition, COO effects have been observed with products in general (Kaynak et al, 2000;Leonidou et al, 1999) as well as with specific product categories (Kim and Pysarchik, 2000;Teas and Agarwal, 2000) and both as regards the behaviour of individual consumers and that of organizational buyers (Ahmed and d'Astous, 1995). Recent research (Laroche et al, 2005;Pereira et al, 2005) using structural equation modelling contends that COO evaluations are part of a larger "COO image" construct consisting of cognitive, affective and conative components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an extrinsic attribute, COO has an influence on consumers' perceptions of a product's quality (Ahmed et al, 2002a, b;Kaynak et al, 2000) and of its attributes (Kim and Pysarchik, 2000;Leonidou et al, 1999), on consumer attitudes towards a product (Lee and Ganesh, 1999), on their perception of risk (Johansson, 1989) and the perceived value of that product (Ahmed and d'Astous, 1996;d'Astous and Ahmed, 1999). COO has also been shown to influence consumer preferences (Knight and Calantone, 2000) and purchase intentions (Kim and Pysarchik, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived product quality was established as a one-dimensional construct and measured by a 7-point semantic differential scale anchored at "The quality of this product is very poor … excellent" (Klein, Ettenson & Morris, 1998). Lastly, the perceived country of origin of the brand was measured by asking respondents to name it as either "local or Chinese" or "foreign", following the lead of Insch and McBride (2004) and Kaynak et al (2000).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have found that COO (Schooler, 1965) has an effect on: attitudes to a product or brand (Lee & Ganesh, 1999;Papadopoulos et al, 1987;Papadopoulos, Heslop & Beracs, 1990;Teas & Agarwal, 2000); evaluation of its attributes and quality (Ahmed et al, 2002;Kaynak, Kucukemiroglu & Hyder, 2000); perception of its value (Teas & Agarwal, 2000); preference for one brand over another (Keown & Casey, 1995;Kim & Pysarchik, 2000); and purchase intentions (Ahmed & d'Astous, 1995;Han, 1989;Lin & Sternquist, 1994;Maher & Carter, 2011;Wang & Yang, 2008;Zhang, 1996).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Literature suggests that COO is a latent factor that assists product evaluation made by consumers (Ahmed and d'Astous, 2004;Kaynak et al, 2000;Nebenzahl and Jaffe, 1996;Srikatanyoo and Gnoth, 2002). Pappu et al (2006) said that brand equity changes as per the change in COO of the product, further argues that marketing managers who operates in the international arena must comprehend the importance of incorporating COO for brand equity measurement.…”
Section: Country Of Originmentioning
confidence: 99%